ORGANIZATIONAL CULTURE IN THE ISLAMIC BOARDING SCHOOL : PHENOMENOLOGY REVIEW - Ahmad Musaddad (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This research focuses on the facts and theories of organizational culture which include: 1) the formation of Salaf culture in modern Islamic boarding schools and 2) the maintenance of Salaf culture in the Modern Islamic boarding schools. This is a qualitative research with a phenomenological approach in the Salafiyah Syafi'iyah Islamic boarding school, Sukorejo, Situbondo. The results showed that organizational culture was formed by the founder's philosophy with the founder's education background and sourced from the salaf books known as four (4) elementary books. The maintenance of the organizational culture is manifested in the activities of the boarding school which include 1) Diniyah school obligations for all students; 2) Establishment of religious-based higher education institutions for mahasantri (Ma'had Aly organization); 3) Obligation to read the yellow book (kitab kuning) and the Koran properly for every student; 4) Obligation to pass basic Madrasah Diniyah; 5) Study of books at various places and times; 6) Wetonan, bandongan and Sorogan methods; 7) Method of muhafadloh or memorization; 8) curriculum system; and, 9) clothing and uniforms.